Mathematical Understanding and Proving Abilities: Experiment With Undergraduate Student By Using Modified Moore Learning Approach - Rippi Maya; Utari Sumarmo (Journal on Mathematics Education, 2011)
This paper reports findings of  a  post test experimental control group design conducted to investigate the role of modified Moore learning approach  on improving students’ mathematical understanding and proving abilities. Subject of study were 56 undergradute students of one state university in Bandung, who took advanced abstract algebra course. Instrument of study were a set test of mathematical understanding ability, a set test of mathematical proving ability, and a set of students’ opinion scale on modified Moore learning approach. Data were analyzed by using two path ANOVA. The study found that proof construction process was more difficult than mathematical understanding  task  for all students, and students still posed some difficulties on constructing mathematical proof task.  The study also found there were not differences  between students’  abilities on mathematical understanding and on proving abilities of  the both classes, and both abilities were classified as mediocre. However, in modified Moore learning approach class there were more students who got above average grades on mathematical understanding than those of conventional class. Moreover, students performed positive  opinion toward  modified Moore learning approach. They  were  active in questioning and solving problems, and in explaining their works in front of class as well, while students of conventional teaching prefered to listen to lecturer’s explanation. The study also found that there was no interaction between learning approach and students’ prior mathematics ability on mathematical understanding and proving abilities,  but  there were  quite strong  association between students’ mathematical understanding and proving abilities.Keywords:  modified Moore learning approach, mathematical understanding ability, mathematical proving ability. DOI: http://dx.doi.org/10.22342/jme.2.2.751.231-250